Na caravela da reflexão: medos, icertezas, descobertas de uma prefessora de inglês - Sousa, Maria Bernadette Nogueira de (2006)
The aim of this research is to investigate how a course for state school English teachers development, called Reflexão sobre a Ação: o Professor de Inglês Aprendendo e Ensinando , may have contributed to change/transform2 my pedagogical practice. For that, I examine some of my own interactions with my 5th, 6th, and 7th grade students of elementary school in different moments (2000, 2002, 2004 before, during and after I had finished the referred course), trying to understand not only what my own role is but also my students . I also want to examine the views of language and of teaching-learning which emerge from my actions in the classroom. The theoretical bases for this study are the development of the reflective teacher proposed by Freire (1970), Freire & Shor (1986), Smyth (1987,1992) and Schön (1992, 2000); Parâmetros Curriculares Nacionais Língua Estrangeira (1998); the interaction in conversational dialogues, proposed by Goffman (1981); the sociointeractionist teaching- learning approach, proposed by Vygotsky (1930/2003, 1934/2000); the language view discussed by Bakhtin (1929/2004, 1979/2003) and the notion of Complexity, according to Morin (2000, 2004, 2005) and Morin & Le Moigne (2000). This work contributed to help myself think critically about my actions and language in the classroom as dynamic factors in the teaching-learning process but not as exclusive or determinant ones, since both teacher and students belong to the complex net of society. The results of the analyses helped observe the repercussion of a development cour se for teachers may have in teaching practice. The change/transformation of a person does not occur at the end of a term; it does not depend on just one factor, but on several interlaced ones, which determine and are determined by the sociohistoric moment